One thousand white women : the journals of May Dodd - Fergus, Jim (New York : St. Martin's Griffin, 2011)
An Indian request in 1854 for 1,000 white brides to ensure peace is secretly approved by the U.S. government in this alternate-history novel. Their journey west is described by May Dodd, a high-society woman released from an asylum where she was incarcerated by her family for an affair.
Includes Reading Group Gold selection (reading group guide).
Includes bibliographical references (p. [435]-436).
Keywords: Little Wolf,-1904 -- Fiction; Interracial marriage -- Fiction; Women pioneers -- Fiction; Cheyenne Indians -- Fiction; Diary fiction; Historical fiction; Western stories; Historical fiction; Western stories